Peran Pengelolaan Pasar dalam Meningkatkan Pendapatan Pedagang Pasar Rakyat Aur Duri - Selamet Rahmadi; Dwi Hastuti (Studium: Jurnal Pengabdian Kepada Masyarakat, 2023)
The primary goal of development is to enhance societal well-being, which is reflected, among other things, through increased income. Merchants in Aur Duri Public Market, located in Penyengat Rendah Village, Telanaipura Subdistrict, Jambi City, play a vital role in the economy and aspire for improved welfare. To achieve this, changes in the management of their business activities are necessary. One effective method to increase income is through counseling. In this community service effort, community-based, persuasive, educative, participative, and normative methods are employed, with a focus on discussion approaches. The choice of these methods is based on the varying educational backgrounds and knowledge of the traders. The results of this service highlight an improvement in traders' understanding and insights on how to boost their income and efforts to create a more conducive environment in the Aur Duri Public Market.